Kepemimpinan Nasional Dan Peran Militer Dalam Proses Demokratisasi - Riswandha Imawan (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2000)
In response to a widespread pressure for political reform, the military has abandon its predominant role in Indonesian politics in the past Yet the incompetence of civilian politician to govern a deep and extensive conflict embedded within the process of democratization, paradoxically, has driven the need for inviting a military